Forming operation in Ge-rich GexSbyTez phase change memories. (July 2017) - Palumbo, Elisabetta; Zuliani, Paola; Borghi, Massimo; Annunziata, Roberto
Highlights: The electrical activation of phase change memories based on Ge-rich Gex Sby Tez is investigated for the first time. The forming operation makes Ge-rich Gex Sby Tez alloys suitable for embedded memories application. Forming current level is shown to have an impact on cell programmability and a physical interpretation is proposed. Forming operation can be tailored according to the requested reliability specifications. Abstract: Optimized Ge-rich Gex Sby Tez materials with improved crystallization temperature have been proven to guarantee code integrity after soldering thermal profile and data retention in extended temperature range for automotive application. Together with higher crystallization temperature, these materials show also peculiar characteristics of the crystalline state with respect to conventional GST (Ge2 Sb2 Te5 ). In particular integrated memory cell shows a very high virgin resistance and needs an electrical activation as last operation of the fabrication process. In this paper we investigate for the first time the role of this electrical activation we named forming operation. In particular we show that the level of the maximum current flowing into the cell at the first electrical activation ( forming level ) has an impact on cell programmability. An explanation of this behavior based on physical analysis is provided suggesting that it is related to the modulation of cell thermal efficiency. Finally it is shown how forming level can be used in order to optimize cell reliability with respect to requested specifications for high temperature data retention (HTDR) and endurance.